2012
DOI: 10.1039/c2ob25142f
|View full text |Cite
|
Sign up to set email alerts
|

Iodine mediated/Brønsted acid-catalyzed dimerization of vinylarenes: a tandem reaction through Ritter trapping to produce N-(4-iodo-1,3-diarylbutyl) acetamides

Abstract: In the presence of p-toluenesulfonic acid and iodine, styrene derivatives undergo head-to-tail dimerization followed by trapping with nitriles to yield the corresponding Ritter-type products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The assistant function of molecular iodine is not only embodied in direct α ‐iodination, but also presented in activating some functional groups. For example, Huang and co‐workers [39] provided a novel dimerization method of styrene derivatives in the presence of Brønsted acid and I 2 to furnish Ritter‐type products (Scheme 17). The molecular iodine activated the vinyl group, just like a reagent with the function I .…”
Section: Oxidizing Component‐induced Reactionsmentioning
confidence: 99%
“…The assistant function of molecular iodine is not only embodied in direct α ‐iodination, but also presented in activating some functional groups. For example, Huang and co‐workers [39] provided a novel dimerization method of styrene derivatives in the presence of Brønsted acid and I 2 to furnish Ritter‐type products (Scheme 17). The molecular iodine activated the vinyl group, just like a reagent with the function I .…”
Section: Oxidizing Component‐induced Reactionsmentioning
confidence: 99%
“…In 2012, Huang et al 32 reported a novel p-toluenesulfonic acid (PTSA, 10 mol%) catalyzed and iodine (100 mol%) mediated head-to-tail dimerization reaction of styrene derivatives and nitriles (Scheme 28). In the presence of p-toluenesulfonic acid and iodine, styrene derivatives undergo head-to-tail dimerization followed by trapping with nitriles to yield the corresponding Ritter-type products.…”
Section: Other Ritter Reactionmentioning
confidence: 99%
“…Many useful compounds have been synthesized through Ritter or Ritter-type reaction, including asymmetrical di-and tri-substituted ureas, 3-substituted-3amino-oxindoles, 4-acyl-aminotetrahydroindazoles, N-(4-iodo-1,3-diarylbutyl) acetamides, 4-amidopiperidine derivatives and aza-bicyclic alkaloids. [4][5][6][7][8]10,11,[13][14][15][16][17][19][20][21][22][23][24]27,[30][31][32][33][34][35][36] This review focuses on new ndings in Ritter or Ritter-type reaction in the last four years and provides a concise overview of recent progress in this area.…”
Section: Introductionmentioning
confidence: 99%
“…This two-component protocol usually involves the generation of carbocation intermediates from tertiary, secondary, and benzylic alcohols under acidic conditions ( Kürti and Czakó, 2005 ). As basic feedstock chemicals, simple alkenes have also been widely used as carbocation precursors in Ritter reaction ( Eren and Kusefoglu, 2005 ; Huang et al., 2012 ; Jiang and Studer, 2020 ; Nandy et al., 2020 ; Park et al., 2018 ; Shi et al., 2015 ; Subba Reddy et al., 2010 ; Welniak, 1996 ; Williams et al., 2017 ; Xu et al., 2017 ; Yang et al., 2018 ; Yasuda and Obora, 2015 ; Zhang et al., 2020 ). Of particular interest is the three-component Ritter reaction, which can efficiently incorporate two distinct functional groups onto the carbon-carbon double bonds in one-step ( Abe et al., 2010 , 2017 ; Ahmed et al., 2020 ; Ai et al., 2015 ; Bao et al., 2019 ; Chen et al., 2016 ; Feng et al., 2018 ; Liu and Klussmann, 2020 ; Qian et al., 2017 ; Zhu et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%